Polyester fiber
The polyester composition with controlled silica particle size and distribution addresses the issues of spinning properties and black color development in existing fibers, achieving enhanced spinning operability and color development.
Patent Information
- Application Number
- JP2020545387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-29
- Filing Date
- 2020-08-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-08-26
AI Technical Summary
Existing polyester fibers and compositions suffer from poor spinning properties and low black color development due to the aggregation of silica particles, leading to increased filtration pressure and insufficient surface roughening.
A polyester composition containing 0.5 to 3.0% by weight of silica particles with an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of 0.40 or less, along with controlled center-to-center distances between silica particles on the fiber surface, to enhance spinning properties and black color development.
The solution provides polyester fibers with improved spinning operability and excellent black color development, suitable for formal uses.
Smart Images

Figure 0007600685000001 
Figure 0007600685000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester composition and a polyester fiber. [Background technology]
[0002] Polyesters, particularly polyethylene terephthalate, are widely used in textile applications. In particular, in the case of fibers for formal wear, it is known that the color development can be improved by roughening the fiber surface in order to reduce the amount of light reflected from the surface and improve black color development.
[0003] In addition, as a method for roughening the fiber surface, adding particles to a polyester composition has been proposed. For example, Patent Document 1 proposes a polyester composition in which the interparticle distance is 0.2-0.7 μm and particles of 50-200 μm are present within the surface. Patent Document 2 proposes a polyester fiber containing 0.4-5 wt % of silica particles with an average primary particle diameter of 0.02-0.1 μm. Patent Document 3 proposes a polyester composition containing 10 ppm-75 ppm of a phosphorus compound, 1-20 ppm of a titanium compound, and 0.5-3.0% of silica particles with an average secondary particle diameter of 20-100 nm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 55-107512 [Patent Document 2] Japanese Patent Application Publication No. 2011-207928 [Patent Document 3] Japanese Patent Publication No. 2013-189521 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the fibers or compositions described in these documents are amorphous bodies formed by agglomeration of particles, and therefore have problems in that the spinnability, such as an increase in filtration pressure during spinning, cannot keep up with the recent trend toward more sophisticated fibers (thinner fibers), and the color development, particularly black color development, is poor.
[0006] Therefore, the present invention provides a polyester composition having excellent spinnability and excellent black coloring property, and a polyester fiber having excellent black coloring property. [Means for solving the problem]
[0007] The object of the present invention is to achieve the above object by any one of the following (1) to (3). (1) A polyester composition containing 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less, and having a methoxy group content of 10 ppm or less. (2) A polyester fiber made of the polyester composition according to (1), comprising 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less, and the silica particles on the fiber surface, the center-to-center distance between adjacent silica particles being in the range of less than twice the average primary particle size, are 10 μm or less. 2 Polyester fibers having four or fewer fibers per unit area. (3) The polyester fiber according to (2) above, wherein the coefficient of friction of the running yarn is 0.35 or less on a yarn-matte surface and 0.7 or less on a yarn-mirror surface. Effect of the Invention
[0008] The polyester composition of the present invention has both good spinnability and black coloring ability, and therefore can provide fibers that are particularly suitable for black formal wear. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. The polyester composition of the present invention contains 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less, and the methoxy group of the polyester is 10 ppm or less.
[0010] The polyester composition of the present invention is a polyester whose main components are an aromatic dicarboxylic acid and a diol.
[0011] The aromatic dicarboxylic acid used in the present invention is preferably 95 mol % or more of an aromatic dicarboxylic acid, and more preferably terephthalic acid.
[0012] In addition, other dicarboxylic acids may be contained as copolymerization components within the range that does not impair the effects of the present invention.Specific examples of known dicarboxylic acids include isophthalic acid, isophthalic acid-5-sulfonate, naphthalene 2,6-dicarboxylic acid, bisphenol dicarboxylic acid, adipic acid, succinic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid.
[0013] The diol used in the present invention is preferably linear alkylene glycol at 80 mol % or more. Specific examples of linear alkylene glycol include ethylene glycol, 1,3-propanediol, and 1,4-butanediol. These may be used alone or in combination of two or more.
[0014] In addition, other diols may be used in combination as copolymerization components within the scope of the present invention that does not impair the effects of the present invention.Specific examples of the diols include diethylene glycol, hexanediol, cyclohexanedimethanol, diethylene glycol bisphenol A ethylene oxide adduct, and polyethylene glycol.
[0015] The polyester composition of the present invention may also contain a matting agent such as titanium dioxide, fine particles such as agglomerated alumina, an antioxidant such as a hindered phenol derivative, and other color pigments.
[0016] The polyester composition of the present invention contains silica particles as described above. The silica particles in the present invention are particles mainly composed of silicon oxide. The silica particles contained in the polyester composition of the present invention have an average primary particle diameter of 0.15 to 0.30 μm. If the average primary particle diameter is greater than 0.30 μm, the surface of the fiber obtained from the polyester composition may be insufficiently roughened, resulting in poor color development. If the average primary particle diameter is less than 0.15 μm, the silica particles may be easily aggregated, resulting in poor spinnability. If the average primary particle diameter is within the above range, both color development and spinnability can be achieved, and if the average primary particle diameter is 0.15 to 0.20 μm, the color development and spinnability are further improved, which is preferable.
[0017] The silica particles contained in the polyester composition of the present invention have the above-mentioned average primary particle size and a relative standard deviation of particle size of not more than 0.40. Here, the relative standard deviation is defined by the following formula. Relative standard deviation = standard deviation of particle size σ / average primary particle size D (μm)
[0018] If the relative standard deviation exceeds 0.40, the amount of silica particles that can contribute to color development on the fiber surface will be reduced, resulting in poor color development, and the fiber surface will become too rough, making it difficult to obtain good spinnability. The relative standard deviation is preferably 0.35 or less, and more preferably 0.30 or less.
[0019] The average primary particle size and relative standard deviation of the silica particles can be determined by subjecting the surface of the polyester composition to low-temperature plasma ashing treatment to a depth of 0.3 μm in a plasma reactor to expose the particles, and processing images of 5,000 or more particles taken with a scanning electron microscope using an image analyzer.
[0020] The polyester composition of the present invention contains 0.5 to 3.0% by weight of silica particles. If the content of silica particles is less than 0.5% by weight, the surface of the fiber obtained from the polyester composition may be insufficiently roughened, resulting in poor color development. If the content of silica particles exceeds 3.0% by weight, the silica particles may be easily aggregated, resulting in poor spinnability. If the content of silica particles is within the above range, both color development and spinnability can be achieved, and if the content is 1.0 to 2.0% by weight, the color development and spinnability are further improved, which is preferable.
[0021] The method for producing the silica particles used in the present invention is not particularly limited, but a wet method is preferably applied.The silica particles can be obtained by hydrolysis using, for example, sodium silicate or alkoxysilane as starting material.From the viewpoint of dispersibility of silica particles and suppression of generation of coarse particles, the silica particles obtained using sodium silicate as starting material are preferred.
[0022] The polyester composition of the present invention can be produced by a conventionally known method, for example, a direct polymerization method. The polyester composition of the present invention contains a polymer.
[0023] The amount of methoxy groups in the polyester composition of the present invention is 10 ppm or less. In order to make the amount of methoxy groups in the polyester composition 10 ppm or less, it is preferable to produce the polyester composition by a direct polymerization method in which aromatic dicarboxylic acid, diol, and other copolymerization components are directly reacted. When the amount of methoxy groups in the polyester composition is 10 ppm or less, the color development is good. The reason why the color development is good when the amount of methoxy groups in the polyester composition is 10 ppm or less is unclear, but it is presumed that this is because when the amount of methoxy groups is small, the amount of diethylene glycol (DEG) and carboxyl terminal groups (COOH terminal groups) tends to increase, and therefore the dye can be attached to the dye.
[0024] In the method for producing polyester fibers from the polyester composition of the present invention, the polyester composition is pre-dried in hot air or under reduced pressure as necessary, and then fed to a spinning machine and spun from a spinneret. In this case, in order to prevent the polyester composition from being deteriorated by heat, the residence time of the polyester composition in the spinning machine is preferably as short as possible, and is usually within 20 minutes. The spinning temperature may be 250 to 300°C.
[0025] The spun yarn is cooled and solidified with cold air, and then an oil is applied thereto, and then the yarn is taken up by a take-up roll that controls the spinning speed. The undrawn yarn taken up by the take-up roll is usually continuously drawn, but it may be drawn in a separate process after being taken up once. The spinning speed may be about 300 to 3000 m / min, and preferably 500 to 2500 m / min. The obtained yarn is false-twisted while being heated as necessary to obtain a polyester textured yarn, and the textured yarn can then be used to produce a knitted fabric using a circular knitting machine.
[0026] In the polyester fiber of the present invention, the number of silica particles on the fiber surface in which the center-to-center distance between adjacent silica particles is less than twice the average primary particle diameter is 10 μm 2 The number of silica particles on the fiber surface that are within a range where the center-to-center distance between adjacent silica particles is less than twice the average primary particle size is 10 μm or less. 2 When the number of particles per unit area is 4 or less, the spinning operability and black coloring property are improved.
[0027] The number of silica particles on the fiber surface with a center-to-center distance of less than twice the average primary particle size is 10 μm 2 In order to make the number of particles per unit area 4 or less, for example, the following method can be used: First, silica particles are diluted with a diol, which is a constituent component of polyester, to 5% by weight or less to form a slurry. Then, between the end of the esterification reaction and the start of the polycondensation reaction, a diol component is added so that the molar ratio of aromatic dicarboxylic acid to diol in the polyester composition after the addition of the silica particles is 2.2 or more, and then the slurried silica particles are added.
[0028] The polyester fiber of the present invention contains 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less. When the average primary particle size is in the above range, the fiber surface is sufficiently roughened, improving color development and excellent spinnability. The average primary particle size is preferably 0.15 to 0.20 μm.
[0029] In the polyester fiber of the present invention, it is preferable that the coefficient of friction of the traveling yarn is 0.35 or less in the yarn-matte finish and 0.7 or less in the yarn-mirror finish, since wear of the guide when forming the yarn path is small.
[0030] The fiber made of the polyester composition of the present invention may be subjected to a weight reduction treatment by a known method, such as plasma treatment, laser treatment, and alkali weight reduction treatment, among which alkali weight reduction treatment is preferred from the viewpoint of the texture and dyeability of the resulting fiber. EXAMPLES
[0031] The present invention will be described in more detail below with reference to examples. The physical properties in the examples were measured by the following methods.
[0032] (1) Average primary particle size, standard deviation, and relative standard deviation The surface of the polyester composition was subjected to low-temperature plasma ashing treatment to a depth of 0.3 μm to expose the particles using a plasma reactor PR300 manufactured by Yamato Scientific Co., Ltd. Images of 5,000 or more particles taken with a scanning electron microscope (SEM, Regulus 8100 type scanning electron microscope: manufactured by Hitachi, Ltd.) were processed with an image analyzer (Image-Pro: manufactured by Nippon Roper Co., Ltd.) to determine the number volume average particle size (average primary particle size), standard deviation, and relative standard deviation. In the case of polyester fibers, after removing the oil, the fiber surface was subjected to low-temperature plasma ashing treatment in the same manner as for the polyester composition to expose the particles, and the particles were then treated with a scanning microscope and image analyzer in the same manner as for the polyester composition.
[0033] (2) Silica particle content (wt%) in polyester composition 6 g of the polyester composition was melted and molded into a plate, and its intensity was measured by fluorescent X-ray analysis using an X-ray fluorescence analyzer (PRIMUS II, manufactured by Rigaku Corporation). The metal content was determined as the silica particle content using a calibration curve previously prepared using samples with known contents. In the case of polyester fibers, after removing the oil, the measurement was carried out by fluorescent X-ray analysis in the same manner as in the case of the polyester composition.
[0034] (3) Methoxy group content of polyester composition 10 ml of hydrazine was added to 20 g of polyester and subjected to alkaline decomposition at 100°C for 40 minutes. The amount of methanol was quantified by gas chromatography, and the equivalent weight / 10 g of polyester was calculated from the measured value. 6 The values are shown in g. In the case of polyester fibers, after removing the oil, the fibers were decomposed with an alkali in the same manner as in the case of the polyester composition, and the content of the oil was measured by gas chromatography.
[0035] (4) Friction coefficient The coefficient of friction of the running yarn was measured with a μMETER manufactured by INTEC and calculated from the tension. The targets were 0.35 or less for the yarn-to-pearly surface and 0.70 or less for the yarn-to-mirror surface, and the evaluation was made on a three-level scale: A: both the matte and mirror surfaces were below the target value, pass; B: either the matte or mirror surface was below the target value, pass; C: both the matte and mirror surfaces exceeded the target value, fail.
[0036] (5) Spinning operability Based on the number of times the yarn broke during spinning, it was rated on a four-point scale: A: Excellent (less than 1 time / t), B: Excellent (1 time / t or more but less than 2 times / t), C: Good (2 times / t or more but less than 3 times / t), and D: Poor (3 times / t or more).
[0037] (6) Black coloring The polyester fibers of the Examples and Comparative Examples were tubularly knitted and treated so that the alkali weight loss rate was 20%. The knitted fabric was then dyed using a 15% owf aqueous dispersion of Dianix Black BG-FS (a disperse dye manufactured by Mitsubishi Chemical Corporation) as the dye, with a bath ratio of 1:30 and at 130°C for 60 minutes. The L value was measured three times using a colorimeter (CM-3700D manufactured by Minolta Co., Ltd.) to calculate the average value, and the L value was evaluated on a four-level scale: A: 12.0 or less, B: more than 12.0 and 13.0 or less, C: more than 13.0 and 14.0 or less, and D: more than 14.0.
[0038] Example 1 A slurry (calculated molar ratio 1.15) consisting of 300 parts by weight of terephthalic acid and 129 parts by weight of ethylene glycol was continuously fed to an esterification reactor equipped with a distillation column over a period of 3 hours while maintaining the reactor temperature at 240 to 245°C, and the reaction was carried out while distilling off water from the upper part of the distillation column. The amount of water distilled off was 64 parts by weight, and the calculated esterification reaction rate of terephthalic acid was 98%. Of the resulting reaction mixture, 43% (volume) was transferred to a polymerization reaction tank while being filtered through a 10 micron filter.
[0039] Then, 22 parts by weight of ethylene glycol was added to the composition transferred to the polymerization reactor, followed immediately by the addition of 0.044 parts by weight of antimony trioxide and 0.16 parts by weight of magnesium acetate. The temperature of the composition was raised to 250°C over about 10 minutes. Then, 22 parts by weight of ethylene glycol was added, followed immediately by the addition of 0.060 parts by weight of trimethyl phosphate. The temperature of the composition was raised to 250°C again over about 10 minutes, after which 22 parts by weight of ethylene glycol was added, and the temperature of the composition was raised to 250°C again over about 10 minutes. Then, a silica slurry (silica particle concentration 5% by weight) consisting of 7.5 parts by weight of silica particles with an average primary particle size of 0.17 μm and a relative standard deviation of particle size of 0.30 and 142 parts by weight of ethylene glycol was divided into three equal parts (volume) and added in three separate portions. In each addition, if the temperature in the system was 225°C or lower, the addition was interrupted, and the system was left on standby until the temperature in the system exceeded 225°C. After each addition, the system was allowed to stand by until the temperature reached 245° C. or higher (the molar ratio of aromatic dicarboxylic acid to diol was 3.0).
[0040] After the addition of the silica slurry was completed, the polymerization reaction tank was heated to 290°C over 90 minutes, and at the same time, the pressure was reduced to 60 Pa over 60 minutes. The polycondensation reaction was carried out until the intrinsic viscosity of the polyester composition, which was previously calculated from the stirring load power, reached 0.66. This polyester composition was dried at 160° C. for 7 hours, spun at a spinning temperature of 290° C. and a spinning speed of 1500 m / min, and then stretched at a draw ratio of 2.81.
[0041] The amount of methoxy groups in the obtained polyester fiber was 5 ppm, the content of silica particles was 1.5% by weight, the average primary particle size was 0.17 μm, the relative standard deviation of the particle size was 0.30, and the number of particles in which the center-to-center distance of the silica particles was less than twice the average primary particle size was 10 μm. 2 The spinning operability, yarn friction coefficient, and black coloring of the fiber were extremely good.
[0042] Example 2 A polyester fiber was obtained in the same manner as in Example 1, except that the average primary particle size of the silica particles was 0.15 μm. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0043] Example 3 A polyester fiber was obtained in the same manner as in Example 1, except that the average primary particle size of the silica particles was 0.20 μm. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0044] Example 4 A polyester fiber was obtained in the same manner as in Example 1, except that the average primary particle size of the silica particles was 0.30 μm. The spinning operability and the yarn friction coefficient were extremely good. The black coloring was at a usable level.
[0045] Example 5 Except for the relative standard deviation of the particle size of the silica particles being 0.40, polyester fibers were obtained in the same manner as in Example 1. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0046] Example 6 Except for changing the content of silica particles in the polyester fiber to 1.0% by weight, a polyester fiber was obtained in the same manner as in Example 1. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0047] Example 7 Except for changing the content of silica particles in the polyester fiber to 2.0% by weight, a polyester fiber was obtained in the same manner as in Example 1. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0048] Example 8 Polyester fibers were obtained in the same manner as in Example 1, except that the content of silica particles in the polyester fibers was 0.5% by weight. The spinning operability and black coloring were extremely good. The yarn-mirror surface friction coefficient was at a usable level.
[0049] Example 9 Polyester fibers were obtained in the same manner as in Example 1, except that the content of silica particles in the polyester fibers was 3.0% by weight. The black coloring was very good. The spinning operability and the yarn-mirror friction coefficient were at a usable level.
[0050] Example 10 After the ester exchange reaction between dimethyl terephthalate and ethylene glycol, the same silica particles as in Example 1 were added, and a polycondensation reaction was carried out in the same manner as in Example 1 to produce a polyester composition (B) (methoxy group content: 20 ppm). To the polyester composition (60 parts by weight) produced in Example 1, 30 parts by weight of the polyester composition (B) was added, and the mixture was spun and drawn in the same manner as in Example 1 to obtain a polyester fiber having a methoxy group content of 10 ppm. The spinning operability, yarn friction coefficient, and black coloring were extremely good.
[0051] Example 11 Polyester fibers were obtained in the same manner as in Example 1, except that the molar ratio of ethylene glycol to terephthalic acid when the silica particles were added was 2.2. The number of silica particles in the obtained polyester fiber in which the center-to-center distance is less than twice the average primary particle size is 10 μm 2 The number of pieces was 4 per 100 pieces. The spinning operability was excellent. The yarn-matte friction coefficient and black coloring were at a usable level.
[0052] The results of Examples 1 to 11 are shown in Table 1.
[0053] [Table 1]
[0054] Comparative Example 1 Except for the fact that the average primary particle size of the silica particles was 0.12 μm, polyester fibers were obtained in the same manner as in Example 1. A large number of aggregates of the silica particles in the obtained polyester fibers were confirmed, and the dispersibility was poor, resulting in poor spinning operability.
[0055] Comparative Example 2 Except for the fact that the average primary particle size of the silica particles was 0.33 μm, polyester fibers were obtained in the same manner as in Example 1. The obtained polyester fibers had poor black coloring properties.
[0056] Comparative Example 3 Except for the fact that the relative standard deviation of the particle size of the silica particles was 0.44, polyester fibers were obtained in the same manner as in Example 1. The spinning operability and black coloring property of the obtained polyester fibers were poor.
[0057] Comparative Example 4 Except for changing the content of silica particles in the polyester fiber to 0.3% by weight, a polyester fiber was obtained in the same manner as in Example 1. The obtained polyester fiber had poor black coloring properties.
[0058] Comparative Example 5 A polyester fiber was obtained in the same manner as in Example 1, except that the content of silica particles in the polyester fiber was set to 3.3% by weight. The obtained polyester fiber had poor spinning operability.
[0059] Comparative Example 6 350 parts by weight of dimethyl terephthalate and 223 parts by weight of ethylene glycol were charged into an ester exchange reaction tank equipped with a rectification column and dissolved at 140°C. Then, 0.044 parts by weight of antimony trioxide and 0.16 parts by weight of magnesium acetate were added, and the temperature of the reaction tank was raised from 140°C to 230°C over three hours. The ester exchange reaction was carried out while distilling off the generated methanol, and then 0.060 parts by weight of trimethyl phosphate was added. 23 parts by weight of ethylene glycol was added to the composition transferred to the polymerization reaction tank (molar ratio 2.2), and a silica slurry (silica particle concentration 5 wt%) consisting of 5.3 parts by weight of silica particles having an average primary particle size of 0.17 μm and a relative standard deviation of particle size of 0.30 and 142 parts by weight of ethylene glycol was divided into three equal parts (by volume) and added in three separate portions. After the addition of the silica slurry was completed, the polymerization reaction tank was heated to 290°C over 90 minutes, and at the same time, the pressure was reduced to 60 Pa over 60 minutes. The polycondensation reaction was carried out until the intrinsic viscosity of the polyester composition, which was previously calculated from the stirring load power, reached 0.66. The obtained polyester composition was spun and stretched in the same manner as in Example 1. The amount of methoxy groups in the obtained polyester fiber was 12 ppm, and the black coloring property was poor.
[0060] Comparative Example 7 Polyester fibers were obtained in the same manner as in Example 1, except that the concentration of the silica particles to be added was 7% by weight and 66 parts by weight of the diol was distilled off before the addition of the silica particles (the molar ratio of the aromatic dicarboxylic acid to the diol after the addition of the silica particles was 2.0). The number of silica particles on the surface of the obtained polyester fiber in which the center-to-center distance is less than twice the average primary particle size is 10 μm 2 The number of particles was 10 per one spin, and both the spinning operability and the black coloring were poor.
[0061] The results of Comparative Examples 1 to 7 are shown in Table 2.
[0062] [Table 2]
[0063] Although the present invention has been described in detail using specific embodiments, it is clear to those skilled in the art that various modifications and variations are possible without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-157115) filed on August 29, 2019, the entirety of which is incorporated by reference.
Claims
1. A polyester fiber made of a polyester composition containing 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less, and having a methoxy group of 10 ppm or less of the polyester, The fiber contains 0.5 to 3.0% by weight of silica particles having an average primary particle size of 0.15 to 0.30 μm and a relative standard deviation of particle size of 0.40 or less, and the silica particles on the fiber surface having a center-to-center distance between adjacent silica particles within a range of less than twice the average primary particle size are 10 μm or less. 2 Polyester fibers having four or less fibers per unit area. The method for measuring the average primary particle size and the relative standard deviation of the particle size of the silica particles is as follows. Using a plasma reactor, the surface of the polyester fiber from which the oil agent has been removed is subjected to low-temperature plasma ashing treatment to a depth of 0.3 μm to expose the particles, and images of 5,000 or more particles taken with a scanning electron microscope are processed with an image analyzer to determine the number volume average particle size (average primary particle size), standard deviation, and relative standard deviation defined by the following formula. Relative standard deviation = standard deviation of particle size / average primary particle size (μm)
2. 2. The polyester fiber according to claim 1, wherein the coefficient of friction of a running yarn is 0.35 or less in a yarn-matte finish and 0.7 or less in a yarn-mirror finish.
Citation Information
Patent Citations
Polyester synthetic fibers and their production
JP1980107512A
Biaxially oriented polyester film
JP1988238135A
polyethylene naphthalate composition
JP1993311051A
Polyester film for magnetic recording medium
JP1996036738A
Polyethylene terephthalate composition and method for producing the same
JP2011207928A
